ANALYTICAL STUDY OF AUTHORS AND TITLES IN MAHANUBHAV LITERATURE BY LANGUAGE - Mankar, Prakash N.; D. W. Devate (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The information collected from the literature sources is available in Marathi, Hindi, English, Sanskrit, Sakal script, Punjabi and Gujarati languages ​​in Maharashtra. Statistical analysis and interpretation of this literature has been done. Accordingly, separate statistical information of the authors and titles of Mahanubhav literature has been prepared and analyzed in descending order and it has been prepared in descending order through analysis tables and graphs. Separate tables and graphs have been prepared and analyzed separately for each language.